Virtual and Augmented Reality Applications in Landscape Design and Project Presentation Techniques - Orhun Soydan; Ahmet Benliay (Turkish Journal of Agriculture: Food Science and Technology)
After realizing that multi-storey buildings are contrary to human nature, the importance of natural landscape and green areas around it has been noticed. For this reason, people want to see how their environment will be in the design phase and the importance of project presentations is increasing day by day. Information technologies for spatial thinking, imagination and modelling have gradually started to be included in landscape design processes. The concept of virtual reality, augmented reality and immersive virtual reality are becoming more and more involved in our lives due to reasons such as the size of the devices getting smaller and their prices being relatively accessible to everyone. As an alternative to traditional presentation techniques and two-dimensional presentation techniques on the computer, making presentations in a virtual reality environment can be a stronger factor in people’s perception of the environment. In the study visual sets in basic, intermediate and advanced level of detail for the same landscape design and project site have been created. Each set consists of hand-drawn perspective image, computer aided perspective image, stereoscopic 360-degree VR image and an augmented reality model. In order to evaluate these visual sets, interviews were made with 10 landscape architects who are experts in the subject. As a result of the study, criteria’s for landscape presentations has been discussed and the advantages and disadvantages of landscape design presentations that will be created using virtual and augmented reality have been evaluated.